Liposoluble Vitamins Importance into Laying Hens Nutrition - Gabriela Maria Cornescu; Tatiana Dumitra Panaite; Arabela Elena Untea; Mara-Ioana Muntiu-Rusu; Ovidiu Avram (Scientific Papers Animal Science and Biotechnologies, 2023)
Liposoluble vitamins play an important role in poultry metabolism. Vitamin A assures normal growth and development, reproduction performances, and immune function. Vitamin D is requested for proper calcium absorption, prevents oxidative stress, and helps the immune system. Also, vitamin E, which cannot be synthesized by poultry, is crucial for growth and reproduction, improves the immunity system, efficient against oxidative stability. Vitamin K is a key factor for the blood clotting process, has anti-inflammatory effects, and improves bone quality and feed efficiency. Vitamin requirements in laying hens' diets increased compared to the minimum levels published 28 years ago in National Research Council, therefore became vital to update it. Due to the poultry and feed industry's increasing challenges and demands the present requirements must sustain the development and productive potential of modern poultry strains. Therefore it is mandatory that experimental data with different inclusion levels of liposoluble vitamins and with positive effects on growth, production, and health parameters be taken into consideration. Certainly, updated information about liposoluble vitamin variability and efficiency transfer rate from diet to egg would help tremendously the farmers interested in foods biofortification by dietary vitamin supplementation. Overall, liposoluble vitamins are considered essential micronutrients very important to assure balanced poultry nutrition that provides an optimized animal status health.